Penanaman Karakter Pada Siswa Melalui Kegiatan Intrakurikuler dan Ekstrakurikuler Di Sekolah Dasar Terpadu Islam - Baidowi, Ach. (EDUCARE: Journal of Primary Education, 2020)
Character education is an effort to foster and shape student character according to school culture. The research objective was to describe the process of cultivating character in students through school intracurricular and extracurricular activities. The research method with qualitative, data collection with interview, observation, and documentation. The results showed (1) character planting through intracurricular activities with (a) strengthening learning, namely character building in accordance with the theme or material, and (b) spiritual paradigm by inserting Islamic values ??in the learning process. (2) character planting through extracurricular activities with (a) scouts, namely forming leadership characters, being independent, solving problems, and loving nature, (b) leadership, forming leadership characters, responsibility, and making decisions, (c) painting, forming detailed, focused, creative characters , (d) martial art, forming tough, skilled characters, (e) reciting recitation, forming religious, moral, orderly characters, (f) child preachers, forming brave characters, positive thinking, art of communication, influencing others. Pendidikan karakter merupakan upaya membina dan membentuk karakter siswa sesuai dengan budaya sekolah. Tujuan penelitian untuk mendeskripsikan proses penanaman karakter siswa melalui kegiatan intrakurikuler dan ekstrakurikuler di sekolah. Metode penelitian dengan kualitatif, teknik pengumpulan data dengan wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukkan: (1) Penanaman karakter melalui kegiatan intrakurikuler dengan cara (a) Penguatan pembelajaran yaitu pembentukan karakter yang sesuai dengan tema atau materi, dan (b) paradigma spriritual dengan menyisipkan nilai keislaman dalam proses pembelajaran. (2) Penanaman karakter melalui kegiatan ekstrakurikuler, (a) Pramuka yaitu membentuk karakter kepemimpinan, mandiri, memecahkan masalah, dan cinta alam, (b) Kepemimpinan, membentuk karakter kepemimpinan, tanggung jawab, dan membuat keputusan, (c) Melukis, membentuk karakter detail, fokus, kreatif, (d) Pencak silat, membentuk karakter tangguh, terampil, (e) Mengaji, membentuk karakter religious, akhlak, tertib, (f) Pendakwah cilik, membentuk karakter berani, berfikir positif, seni komunikasi, mempengaruhi orang lain.